Performance of supercapacitor with electrodepo sited ruthenium oxide film electrodes - Effect of film thickness - Park, BO; Lokhande, CD; Park, HS; Jung, KD; Joo, OS (ELSEVIER SCIENCE BV, 2004)
Thin-film ruthenium oxide electrodes are prepared by cathodic electrodeposition on a titanium substrate. Different deposition periods are used to obtain different film thicknesses. The electrodes are used to form a supercapacitor with a 0.5 M H2SO4 electrolyte. The specific capacitance and charge-discharge periods are found to be dependent on the electrode thickness. A maximum specific capacitance of 788 F g(-1) is achieved with an electrode thickness of 0.0014 g cm(-2). These results are explained by considering the morphological changes that take place with increasing film thickness. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: HYDROUS RUTHENIUM; ELECTROCHEMICAL SUPERCAPACITORS; CAPACITORS; DEPOSITION